Impact of Screening Implementing HCV Screening of Persons Born 1945-1965 - James Gemelas; Rachel Locker; Stephen Rudd; Carol Prevost; Brigg Reilley; Jessica Leston (Journal of Primary Care & Community Health, 2016)
Background: In August 2012, the Centers for Disease Control and Prevention released recommendations to screen persons born from 1945 to 1965 for hepatitis C virus (HCV). In September 2012, Warm Springs Health and Wellness Center (WSHWC) initiated a quality improvement (QI) project to conduct HCV screening among all patients in this birth cohort. Methods: Screening rates were tracked using a nationally standardized HCV screening measure in the Indian Health Service. At the end of the project period, WSHWC staff took a brief survey to review the impact of the HCV QI Project. Results: Screening for HCV among eligible patients at WSHWC increased from 5% (47/938) in September 2012 to 76% (593/785) in September 2014. Survey data indicated that clinicians felt increased screening for HCV had a positive impact on patient communication and care. Conclusions: Primary care clinics can successfully increase HCV screening in a relatively short time period. Age based screening recommendation may provide opportunities to increase communication with others at risk for HCV. As more patients are screened, it will be important to ensure appropriate linkage to care for HCV patients.